Design and Implementation Driving Circuit of High Power 980 nm Laser Diode - Al-Jumaily, A.K.; Mansour, T.S (Iraqi Journal of Laser, 2025)
Laser diode with 980 nm has many attractive applications in telecommunication and photonic systems especially when it used for pumping the Erbium–Doped Fiber Amplifiers (EDFAs) which is an essential c- band amplifier that used in many applications for enhancing the nonlinear system conversion efficiency. In this work pulsed laser diode was manufactured after electronically implement the divider circuit with thermal stability of 14 pin 980 nm butterfly laser diode (AGREE SL 90S31A) that has maximum power of 160 mW. This driver circuit was based on the LM317 adjustable current regulator. The electronically chopped 980 nm laser diode achieved stable modulation in the frequency range from 1 Hz to 1 kHz. The proposed driver circuit is simple, low-cost, and successfully provides the required optical modulation for tapered fiber interferometer applications, making it a practical alternative to expensive electro-optic modulation systems such as commercial Lithium Niobate electro-optic modulators which are costly and also require expensive drivers to operate.